2016
DOI: 10.1016/j.ijrmms.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale approach for modeling the transversely isotropic elastic properties of shale considering multi-inclusions and interfacial transition zone

Abstract: Copies of full items can be used for personal research or study, educational, or not-for-profit purposes without prior permission or charge. Provided that the authors, title and full bibliographic details are credited, a hyperlink and/or URL is given for the original metadata page and the content is not changed in any way. A note on versions:The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…Anisotropy has been included in some of these numerical simulations by decreasing the values of mechanical properties, such as elastic modulus, cohesion coefficients or fracture toughness, in precise locations of the domain in order to create weak layers which affect fracture extents and shapes. However, Chen et al (2016) showed that the introduction of weak bands is not enough to entirely reproduce the real anisotropic mechanical response of the shale rocks. It should be considered that in addition to the presence of the voids and microfractures, there are many types of inclusions, such as quartz, calcite and dolomite, forming a locally heterogeneous structure for the shales.…”
Section: Introductionmentioning
confidence: 99%
“…Anisotropy has been included in some of these numerical simulations by decreasing the values of mechanical properties, such as elastic modulus, cohesion coefficients or fracture toughness, in precise locations of the domain in order to create weak layers which affect fracture extents and shapes. However, Chen et al (2016) showed that the introduction of weak bands is not enough to entirely reproduce the real anisotropic mechanical response of the shale rocks. It should be considered that in addition to the presence of the voids and microfractures, there are many types of inclusions, such as quartz, calcite and dolomite, forming a locally heterogeneous structure for the shales.…”
Section: Introductionmentioning
confidence: 99%
“…The Micromechanical Approaches to Represent the Imperfect Bonding. There are mainly two analytical models to represent the imperfect bonding between the inclusion phase and matrix phase [23][24][25][26][27]. One is the spring layer model, also known as the interface model, which involves a very thin interfacial zone of unspecified thickness [23][24][25].…”
Section: Micromechanical Model For Saturated Concrete Repaired Using mentioning
confidence: 99%
“…One is the spring layer model, also known as the interface model, which involves a very thin interfacial zone of unspecified thickness [23][24][25]. The other is the interphase model, which describes the interfacial zone as a layer between particles and matrix of a specified thickness and of elastic constants different from those of the matrix and the particles [26,27]. In this paper, the interphase model is utilized to represent the imperfect bonding between the deposition products and the intrinsic concrete matrix.…”
Section: Micromechanical Model For Saturated Concrete Repaired Using mentioning
confidence: 99%
“…Since macroscopic rock failure is attributed to complicated micromechanisms that are involved in the cracking process (Hajiabdolmajid & Kaiser, ), reliable interpretation of the microscopic fracturing mechanism relies on an in‐depth knowledge of the effects of grain‐scale structures. Chen et al () found that the introduction of weak bands is insufficient to capture the entire anisotropic mechanical behavior of transversely isotropic shale rocks, while other types of inclusions (e.g., quartz, calcite, and dolomite) forming local heterogeneity should also be considered. Meng and Pan () presented quantitative correlations between mineral compositions and failure duration, microstructures, and failure duration, which indicate significant reliance of macromechanical properties of rocks on their petrographic characteristics.…”
Section: Introductionmentioning
confidence: 99%